Angiographic Predictors for Repeated Revascularization in Patients with Intermediate Coronary Lesions - Yong-Kyun Kim; Soon-Ho Kwon; Young-Hoon Seo; Ki-Hong Kim; Taek-Geun Kwon; Jang-Ho Bae (Biomedicines)
Background: Intermediate lesions (ILs) present challenges in making therapeutic decisions. This study aimed to determine the practical coronary angiographic predictors for revascularization in patients with ILs who underwent repeated angiograms. Methods: This study was a retrospective single-center study. The study subjects were divided into two groups according to their target lesion revascularization (TLR) during the follow-up period: the TLR (+) group (n = 135, 30.9%) and the TLR (−) group (n = 302, 69.1%). We evaluated the angiographic characteristics of ILs such as the presence of branches, luminal irregularity, tortuosity, ulcer/erosion, haziness, and calcification in the ILs, with an average follow-up of 34.2 ± 32.0 months. Results: The TLR (+) group had higher percentage of diameter stenoses (47.3 ± 13.5% vs. 44.2 ± 12.2%, p = 0.006) than the TLR (−) group, whereas the lesion length of the ILs showed no significant differences between the two groups. The prevalence of branches (79.0% vs. 69.1%, p = 0.018) and haziness (4.3% vs. 2.6%, p < 0.001) was higher in the ILs of the TLR (+) group than those of the TLR (−) group. Therefore, the angiographic predictors for the TLR of ILs were haziness (hazard ratio = 2.126, 95% confidence interval = 1.240–3.644, p = 0.006) and % diameter stenosis (DS) ≥ 60% (hazard ratio = 1.025, 95% confidence interval = 1.013–1.037, p < 0.001). Conclusions: Angiographic haziness and % DS > 60% were the independent angiographic predictors for TLR in patients with ILs. Our study is the first to present the angiographic findings of vulnerable plaques of ILs. Further studies such as intravascular imaging or physiologic studies should be strongly considered before making treatment decisions in ILs when such angiographic features are observed.